BUDAYA ISLAM VERSUS ISLAMISASI BUDAYA DALAM PERSPEKTIF GENERASI ZILENIAL - Muhamad Parhan; Muhammad Rofiudin; Isma Afina Salsabila; Shofa Sofia Rohimat; Bilqisty Nur Arasshifa; Putri Aghniya Dhitareka (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Islamic culture and religion are two things that always go hand in hand and synergize in human life or Muslims. However, the phenomena and problems that exist in society today are that Islam and culture are too mixed up, causing problems in society such as the loss of direction of Islamic teachings that are sourced from the Qur'an and hadith. This study aims to reveal the perspective of the millennial generation on the phenomenon of Islam being cultured and culture being Islamicized, whether they go hand in hand and synergize in life or are they a source of division. The research approach uses a quantitative, data collection technique using a Likert Scale which is disseminated online via google form. The subjects in this study were the Zillenial Generation. The results showed that the millennial generation had seen and carried out Islamic civilizing activities or Islamic culture. The opinion of the millennial generation towards this phenomenon is very much in agreement with the phenomenon of Islamic civilisation. Meanwhile, the majority of the opinion responses of the Zilenial generation show a neutral attitude towards the phenomenon of cultural Islamization. However, there are still responses that agree or even strongly agree. This shows that the millennial generation already understands cultural and Islamic phenomena.